Proceedings of the International Conference on Interdisciplinary Studies (ICIS 2016) Interdisciplinarity and Creativity in the Knowledge Society - Mihaela Pomazan, Valentina (IntechOpen, 2016)
Interdisciplinarity is a sine qua non condition for any modern endeavour, a reason for the International Conference on Interdisciplinary Studies (ICIS 2016) to promote new and emerging research topics and interdisciplinary collaborations. During the event experiences about how interdisciplinary research is carried out were summarized and the demand for interdisciplinary research and innovation was investigated. The 2016 edition aimed also to get an in-depth view of the solutions to provide the skills required for real advancement of our society, to emphasize the social need for creative thinking and innovation and to investigate the role creative thinking plays in producing new, integrative knowledge. The present volume summarizes the most relevant papers accepted for presentation during ICIS 2016, held at Ovidius University of Constanta, Romania, between 10 and 11 June 2016.